Mausolée, sarcophage et scène de sacrifice dans une ferme antique à Pommiers, près d’Anse (Rhône) - Jean-Claude Béal (Gallia, 2018)
Rescue excavations carried out in the commune of Pommiers (Rhône), near the Asa Paulini (Anse) relay station, yielded a sarcophagus and a sculpted relief near a building identified as a mausoleum, built at the edge of a Gallo-Roman farm. The relief shows a sacrificial scene in the Roman tradition, unrelated to the usual images of sacrifice in Gaul. It can be dated to the first decades of the 2nd century. The sarcophagus is made of the same material and might be contemporary or from a later period. The man offering the sacrifice appears to be a notable, possibly a sevir, and this scene demonstrates his economic and social position.